Be Kind Rewind: Navigating Issues of Access and Practising an Ethics of Care for Magnetic Media from Vulnerable Communities - Gilmore, Julia (Archivaria)

(untitled) (Association of Canadian Archivists, 2023)
Magnetic media, once democratizing documentary tools for marginalized communities, now face degralescence due to the physical degradation of magnetic tape and the obsolescence of playback equipment. However, these are not the only concerns when it comes to these media; while digitizing and providing online access have increasingly become requirements for major funding bodies and strategies adopted by archives, the contemporary neoliberal orientation toward open, online access poses additional risks for vulnerable communities.The impending magnetic media crisis presents a critical opportunity to contend with neoliberal archival impulses; re-envision approaches to preservation, digitization, and access; and acknowledge the affective values of magnetic media for communities who have produced and cared for them. Largely unexplored in archival literature, the unique promise and precarity of magnetic media created by vulnerable communities require ethical consideration of issues of privacy, exposure, and decontextualization and an understanding of the complexities of preserving magnetic media. This article explores these considerations and issues, advocates for the adoption of a feminist ethics of care, and introduces the VHS Archives Working Group as a generative model for caring for magnetic media from vulnerable communities.